Chemistry does general relativity: reaction-diffusion waves can model gravitational lensing - Cohen-Cobos, Daniel; Sanders, Kiyomi; DeGroot, Laura; Guarnera, Heather; Leary, Cody; Lindner, John F.; Manz, Niklas (Frontiers in Physics, 2024)
Gravitational lensing is a general relativistic (GR) phenomenon where a massive object redirects light, deflecting, magnifying, and sometimes multiplying its source. We use the chemistry of Belousov-Zhabotinsky (BZ) reaction-diffusion (RD) waves to study this astronomical effect in a table-top experiment. We begin by experimentally passing RD waves through non-planar quasitwo-dimensional molds. We next reproduce the waveforms in computer simulations of planar RD waves with variable diffusion. We then vary the diffusion parameter so the effective wave speed of planar waves matches the GR predictions for light deflection near a massive object. We thereby recover Einstein's famous light deflection formula.